PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA BODY SHAMING DI MEDIA SOSIAL DALAM PERSPEKTIF VIKTIMOLOGI - Simangunsong, Ronald; Borman, M. Syahrul; Handayati, Nur (COMMUNITY OF RESEARCH LABORATORY (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN), 2024)
This study aims to analyze the form of legal protection for victims of body shaming crimes on social media in the perspective of victimology and the urgency of legal protection. The research method used is normative juridical. The results show that legal protection for victims of body shaming crimes in social media can be seen from the provisions in Law No. 13 of 2006, LPSK Regulation Number 6 of 2010, and article 27 paragraph 3 of the ITE Law. However, the current regulations are considered ineffective to overcome the problem of body shaming on social media. The majority of respondents expressed dissatisfaction with the imposition of criminal penalties alone and advocated for social sanctions as well. In addition, the complexity of the legal process is considered to be one of the factors for victims' reluctance to report. The urgency of providing legal protection for victims of body shaming crimes on social media is very high, given the significant psychological impact on victims. In addition, there are still many perpetrators who do not realize the consequences of body shaming. The government has implemented legal protection measures for victims as a form of commitment to protect the community, which can be in the form of compensation, restitution, and other forms of compensation.